Genome wide association study identifies a novel putative mammographic density locus at 1q12‐q21. Issue 10 (10th November 2014) - Fernandez‐Navarro, Pablo; González‐Neira, Anna; Pita, Guillermo; Díaz‐Uriarte, Ramón; Tais Moreno, Leticia; Ederra, María; Pedraz‐Pingarrón, Carmen; Sánchez‐Contador, Carmen; Vázquez‐Carrete, Jose Antonio; Moreo, Pilar; Vidal, Carmen; Salas‐Trejo, Dolores; et al.
<x xml:space="preserve">Abstract</x> Mammographic density (MD) is an intermediate phenotype for breast cancer. Previous studies have identified genetic variants associated with MD; however, much of the genetic contribution to MD is unexplained. We conducted a two‐stage genome‐wide association analysis among the participants in the "Determinants of Density in Mammographies in Spain" study, together with a replication analysis in women from the Australian MD Twins and Sisters Study. Our discovery set covered a total of 3, 351 Caucasian women aged 45 to 68 years, recruited from Spanish breast cancer screening centres. MD was blindly assessed by a single reader using Boyd's scale. A two‐stage approach was employed, including a feature selection phase exploring 575, 374 SNPs in 239 pairs of women with extreme phenotypes and a verification stage for the 183 selected SNPs in the remaining sample (2, 873 women). Replication was conducted in 1, 786 women aged 40 to 70 years old recruited via the Australian Twin Registry, where MD were measured using Cumulus‐3.0, assessing 14 SNPs with a p value <0.10 in stage 2. Finally, two genetic variants in high linkage disequilibrium with our best hit were studied using the whole Spanish sample. Evidence of association with MD was found for variant rs11205277 (OR = 0.74; 95% CI = 0.67–0.81; p = 1.33 × 10−10). In replication analysis, only a marginal association between this SNP and absolute dense area was found. There were also evidence of association between MD and SNPs in high linkage disequilibrium with rs11205277, rs11205303 in gene MTMR11 (OR = 0.73; 95% CI = 0.66–0.80; p = 2.64 × 10−11) and rs67807996 in gene OTUD7B (OR = 0.72; 95% CI = 0.66–0.80; p = 2.03 × 10−11). Our findings provide additional evidence on common genetic variations that may contribute to MD.